Shamanic medicine: analysis from a scientific perspective - Musso, Carlos G. (Revista del Hospital Italiano de Buenos Aires, 2015)
Shamanic activity has been documented in all hunter-gatherer societies past and present without exception. The role of the shaman is primarily characterized by dominating the ecstatic experience, a trance where the shaman believes make his soul leaves his body acquiring the ability to explore the level of spirits, which in his view is the basis of his power healing and control over the forces of nature. Modern sciece has proposed rational explanations about what would be the foundations on which two of the central features of shamanic medicine are based: the generation of ecstatic state by the shaman and his potential healing power. With regard to the ecstatic state it would be the development of a state of altered perception itself of the human mind led by personal factors (diseases), environmental (inhospitable environments) and / or pharmacological (psychotropic agents); while the shaman healing effects could be attributed to the symbolic efficiency of rituals